(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
The article presents the results of an experimental study in an experimental setup, a drum wet dust cleaning apparatus under various gas and liquid flow regimes. The local and general coefficients of resistance and the loss of total pressures in the working sections of the device are determined. As a result, depending on these pressures, it is possible to determine the optimal values of the efficiency of dust and gas cleaning and the energy consumption of the device.